Artifacts, Visual Modeling and Constructionism: To Look More Closely, to Watch What Happens - Clayson, James E. (Problemos, 2018)
[full article, abstract in English; abstract in Lithuanian]Constructionists operationalize a powerful notion they share with constructivists: individual learning is facilitated by building models of specific ideas, concepts, methods, objects, environments, feelings, dreams, memories and sounds using the learner’s current stock of knowledge. Constructionists do this by building models or artifacts that can be externally manipulated, interrogated by their builder, and verbally shared with others. Constructionists believe that new knowledge is created during these discussions. Constructionism is rich with heuristic methods for both finding and constructing artifacts and for discussing these artifacts privately and publicly. Constructionists argue that both constructing and discussing are necessary for deep sense-making.This paper describes one specific constructionist learning method: visual modeling. It illustrates one educator’s approach, developed in the classroom over a 40-year period. It references the relevant literature; describes its pedagogic approach, materials and outcomes; and it offers a step-by-step example of one student’s thinking process. Finally, it presents – in appropriate narrative form – 15 arguments why the visual component extends the constructionist project and should be integrated into more educational programs.
Keywords: constructionism; visual modeling; transformational objects; artifacts; drawing; narrative psychology